G. Ligeti’s Hamburg Concerto as a Summary of Late Artistic Tendencies - Zharkova, Valeriya; Zharkov, Oleksandr; Antonova, Olena; Filatova, Tetiana; Rizaieva, Ganna (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
The relevance of this study is conditioned upon the need to highlight the internal content of the modern academic musical language and, specifically, the features of the late work of G. Ligeti. This paper aimed to conduct an in-depth study, comprehensively covering, analyzing, and generalizing the panoramic display of the creative traditions of G. Ligeti in the context of world musical art. The materials of this paper are sources that illuminate the path of stylistic search and the evolution of the musician’s composition, as well as information about the leading directions of the modern world academic musical environment. The research methods included a search and collection of information base dedicated to the Hamburg Concerto by G. Ligeti; analysis and compilation of available materials; determination of the leading categories of the phenomenon presented in the late period of the composer’s work; showing his stylistic and compositional principles as a single multifaceted system. The result of the study was the individual author’s concept of vision of the role, significance, and content of G. Ligeti’s work in the history of academic musical art. The practical significance of this study was manifested in the demand for the results of this study among students of secondary and higher musical educational institutions, as well as among specialists investigating the processes of transformation and expansion of the boundaries of the melodic, compositional, and technical arsenal of professional musical creativity.